Theory of international economic relations (part 2) - Syshchuk, Andrii A. (Lesya Ukrainka Eastern European National University, 2019)
The content of the course "Theory of International Economic Relations" is the disclosure of the general basics and history of development of the international economy, the study of essential features and analysis of the major trends in the development of international economic relations in the fields of international trade, international capital movement, international migration of labor, monetary and financial relations, international technology transfer and international economic integration, study of laws, laws and features of development of international economic relations son in modern conditions.
Keywords: types of monetary systems; World currency system; structure of the international financial market; risks of monetary and financial transactions; the international debt market; monetary policy; exchange rate regulation; regulation of the International Macroeconomics